Simulation of The Heat Transfer Process Inside The Thatch Walls with The Aim of Saving Energy in The Buildings - Hadi Baseri; Hamid Reza Nassehinia; Gholamreza Ghaeiny (Iranian Journal of Health, Safety and Environment, 2016)
The insulation is one of the emphasized methods in recent years to reduce energy consumption in buildings. As an insulator, thatch has the advantages such as the accessibility of the site, the least energy consumption in its construction (low cost), recyclability and compatible with the nature and the environment. The aim of this study is determining of the heat transfer coefficient and thatch mechanical properties So that due to its advantages it used as insulation and thereby reducing energy consumption in buildings considered and used. In this study, the heat transfer process in a cylindrical turn of thatch was studied. In the conducted experiments the temperature changes inside a cylinder turn were determined for different values of the ratio of the Straw to the used soil and then the obtained results were simulated using the version 2.4 of the COMSOL software. The compressive strength and mechanical properties of thatch were tested. By increasing the consumed Straw weight of 50 to 90 kg per 1 cubic meter of soil, the heat conductivity coefficient from about 1.1 decreased to about 0.3 (W/m K), the contraction percentage decreased and the porous, the compressive strength and the thatch deformability increased in the failure. Thermal insulation and the mechanical properties of the thatch were improved by the mixing of appropriate ratio of straw to soil in the construction of thatch. It can be used in the plaster of the walls and the internal and external ceilings of the building.